(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
This is the necessary and sucient conditions to the regularity of solution of elliptic problems on non smooth domains in R3 . I study a boundary value problem for elliptic partial dierential equation. I study the regularity of solution to the problem in non smooth domain. I obtain the necessary and sucient conditions of the problem to belong to Cm+2+: